Close relationships : what couple therapists can learn - Hendrick, Susan (Pacific Grove, Calif. : Brooks/ Cole Pub. Co., 1995)
Takes the research area of close relationships and applies it to couples counselling. Topics such as love, power, divorce and remarriage are explored from the close relationships perspective. The book aims to bring together the worlds of the close relationships scholar and the couples therapist.
Includes bibliographical references and index.
Keywords: Marriage counselling; Unmarried couples -- Counseling .